Observation on Therapeutic Effect of Scalp Acupuncture Combined with Transcutaneous Electric Nerve Stimulation on Thalamic Pain - Xingyue FAN; Bo LIU; Weisong ZHANG (康复学报)
Objective:To observe the therapeutic effect of scalp acupuncture combined with transcutaneous electric nerve stimulation on treating thalamic pain.Methods:Sixty patients in thalamic hemorrhage associated with thalamic pain were assigned to the treatment group and control group by a random number table, and 30 patients in each group. While their condition was stable, the two groups received scalp acupuncture and rehabilitation training for a month, and the treatment group was added with transcutaneous electric nerve stimulation, once a day. Ten days of treatment composed a treating course, and the complete treatment lasted for three courses. The visual analogue scale (VAS) for pain degree, simplified Fugl-Meyer assessment (FMA) on motor function and Barthel index (BI) for activities of daily living (ADL) were used to evaluate the therapeutic effect before and after interventions and compared between the two groups.Results:The VAS was decreased, the FMA and BI scores were increased after the treatment in both groups (P<0.05). After the treatment, the VAS in the treatment group was lower than that of control group, and the FMA and BI scores were higher than those of control group (P<0.05).Conclusion:Scalp acupuncture, rehabilitation therapy combined with transcutaneous electric nerve stimulation can reduce the degree of pain, improve the limb motor function of thalamic pain patients, so as to further improve their daily life abilities than scalp acupuncture with rehabilitation therapy.